The fate of a scientist: Bashir Iskandarovich Rameev - Taisiya Yu. Novinskaya (Историческая этнология, 2023)
The article is dedicated to the life and work of Bashir Iskandarovich Rameev, one of the founders of domestic computer technology in the USSR, whose professional activities were closely connected with the city of Penza. In the 1950s, the largest research institute for electronic computing machines was established based on the SAM plant in Penza. The article focuses on the scientist's life path, which reflects the history of the country – the revolution of 1917, repressions, the Great Patriotic War, the achievements of Soviet science and technology in the post-war years in the setting of the Cold War. The formation of B.I. Rameev as a scientist coincided with the development of the first information technologies – the development of the first domestic computer “Strela”. The creation of a galaxy of electronic computing machines “Ural” falls on the peak of his career, when the scientist fullfilled the “principle of programmatic and constructive compatibility”.